Interweaving Theory and Practice. The significance of Galtung’s editorials - Erika Degortes (Revista de Cultura de Paz)
This article explores the interplay between theoretical frameworks and practical applications in Johan Galtung’s editorials, published on TRANSCEND Media Service (TMS). It presents specific examples where Galtung addresses real-world conflicts and proposes solutions, highlighting the impact of his work in both academic and practical contexts. The article examines Galtung’s theoretical contributions, focused on preventing violence rather than conflicts, demonstrating how his editorials serve as practical embodiments of these theories. Through the analysis of his editorials, Galtung's approach to conflict transformation and the contemporary relevance of his theories are revealed. Conflict work, as described by Galtung (2000), is an art that blends optimism, idealism, and realism. This philosophy underpins the TRANSCEND method, which seeks solutions that create an appealing reality for all parties involved in a conflict. Ultimately, Galtung's editorials underscore the importance of addressing underlying issues and promoting dialogue and cooperation as pathways to peace.